A Terrestrial Thermometer Using Carbonate Clumped Isotopes From Gar Scales - Katelyn E. Gray; Mark T. Brandon (Geochemistry, Geophysics, Geosystems)
Abstract We present a new clumped isotope calibration relating temperature to the Δ47 composition of the bioapatite scales of gar fish (Lepisosteidae family). Modern gars live at <∼3 m depth in rivers and lakes, are non‐migratory, and their scales grow continuously over their lifespan (∼8–14 years). As ectotherms, their body temperature is equivalent to ambient water temperature. These features indicate that the Δ47 composition of gar scales may be useful for measuring the surface temperature in present and past terrestrial settings. Fossil gar scales are widely distributed in time (Cretaceous to modern) and location (North and South America, Europe, India, and Africa), and are highly mineralized and resistant to diagenesis. Our calibration is based on modern gars collected from eight locations in North America. We use climate data to convert the variable temperature in the gar's habitat into an effective temperature, Te, to account for variable growth. For our samples, Te ranges from 13.8 to 27.1°C. We report a lab protocol for measuring the Δ47 composition of gar scale bioapatite with a reproducibility of 0.019‰ (1 SD). Our calibration is based on 19 samples, with ∼3 replicate measurements per sample. The result is Δ47 = (0.1206 ± 0.0171) × 106/Te2 – (0.7429 ± 0.0587) (1 SE), with R2 = 0.75 (Δ47 in ‰ and Te in K). The slope of this calibration is steeper than that for the lab‐controlled precipitation of inorganic carbonate. We argue that this difference is caused by kinetic isotope effects associated with hydroxyapatite biosynthesis.